2012
DOI: 10.1371/journal.pone.0044855
|View full text |Cite
|
Sign up to set email alerts
|

Differential Proteomics and Functional Research following Gene Therapy in a Mouse Model of Leber Congenital Amaurosis

Abstract: Leber congenital amaurosis (LCA) is one of the most severe forms of inherited retinal degeneration and can be caused by mutations in at least 15 different genes. To clarify the proteomic differences in LCA eyes, a cohort of retinal degeneration 12 (rd12) mice, an LCA2 model caused by a mutation in the RPE65 gene, were injected subretinally with an AAV vector (scAAV5-smCBA-hRPE65) in one eye, while the contralateral eye served as a control. Proteomics were compared between untreated rd12 and normal control reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
(52 reference statements)
3
16
0
Order By: Relevance
“…The mRNA and protein expression and enzymatic activity of PRDX6 markedly increase in the mouse when exposed to 100% oxygen [33]. Additionally, two-dimensional electrophoresis and mass spectrometry analyses of retinas of mice with HRD indicated higher PRDX6 expression [34]. In the present study, we demonstrated for the first time that PRDX6 could protect ARPE-19 cells against oxidative damage by H 2 O 2 .…”
Section: Discussionsupporting
confidence: 54%
“…The mRNA and protein expression and enzymatic activity of PRDX6 markedly increase in the mouse when exposed to 100% oxygen [33]. Additionally, two-dimensional electrophoresis and mass spectrometry analyses of retinas of mice with HRD indicated higher PRDX6 expression [34]. In the present study, we demonstrated for the first time that PRDX6 could protect ARPE-19 cells against oxidative damage by H 2 O 2 .…”
Section: Discussionsupporting
confidence: 54%
“…Similar experiments in mutant mice treated early with gene therapy have shown survival of cone (12,13,15,16) and rod photoreceptors (49). Investigation of the mechanism(s) causing photoreceptor cell loss (18,(53)(54)(55)(56) has been mostly performed in untreated eyes to date. Extension of such studies to eyes undergoing gene therapy (18) would be important to clarify molecular underpinnings of the observed modification of natural history.…”
Section: Discussionmentioning
confidence: 94%
“…Investigation of the mechanism(s) causing photoreceptor cell loss (18,(53)(54)(55)(56) has been mostly performed in untreated eyes to date. Extension of such studies to eyes undergoing gene therapy (18) would be important to clarify molecular underpinnings of the observed modification of natural history. Furthermore, the newly discovered vitamin A isomerization pathway originating in Muller cells and subserving cones (57) may be found to contribute to the differences in (cone or rod) photoreceptor survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations